Family structure and modern contraceptive use among women in Malawi - Chibuye, Ng'andwe (My University, 2016)
Background Contraceptive prevalence in sub-Saharan Africa is low compared to other regions of the world. Despite this, some countries within the sub-Saharan African region, such as Malawi, have been identified as champions of contraceptive use within the region but still face many reproductive health challenges, such as a high total fertility rate of 5.7 births per woman (Malawi Demographic and Health Survey (MDHS), 2011). The purpose of the study is to examine the prevalence of the use of modern contraception given different dimensions of family structure and what significant relevance this may have in creating contextually appropriate family planning interventions. A literature search of studies on family structure in Africa shows little evidence of such a study in Malawi. Methodology The study was cross-sectional and made use of the 2010 Malawi Demographic and Health Survey (MDHS). It focused on women of reproductive ages (15-49 years). A total of 12, 490 women made the sample of the study. In order to address the objectives, descriptive statistics and chi-square tests were conducted to assess the levels and patterns of modern contraceptive use in Malawi. Lastly, binary logistic regression was carried out in order to test the association between different dimensions of family structure and modern contraceptive use. Results The study established that the prevalence of modern contraceptive use in women of reproductive age (15-49) in Malawi was estimated at 48%. The study showed that family structure did have an influence on modern contraceptive use. Specifically the likelihood of modern contraceptive use was higher among women with larger family sizes. The association between sex composition of children and modern contraceptives was also significant. Findings further showed that women in female-headed households were less likely to use modern contraceptives compared to women in male-headed households. Conclusion Family structure was found to have an influence on modern contraceptive use in Malawi. The study findings have implications towards achieving the reproductive goals of the Malawi Growth and Development Strategy (2011-2016) and the Malawi Health Sector Strategy Plan of (2011-2016) or future policies which have important reproductive health goals for women.
Keywords: Contraceptives; Family planning